PRE-INSPECTION AUDITS IN COMPLIANCE WITH FEDERAL HOUSING QUALITY STANDARDS IN SUBSIDIZED PROJECTS: A SYSTEMATIC REVIEW - Carolini Catunda Bispo, Daphne (Humanas em Perspectiva, 2026)
This article presents a systematic literature review on the effectiveness of pre-inspection audits in ensuring compliance with federal housing quality standards in subsidized projects. The research covered publications from the period of 2021 to 2025, analyzing the Brazilian Minha Casa Minha Vida (MCMV) programs and the Conformity Assessment System (SiAC) of PBQP-H, alongside the North American National Standards for the Physical Inspection of Real Estate (NSPIRE) and Low-Income Housing Tax Credit (LIHTC). The results demonstrate that the proactive identification of non-conformities through preventive audits substantially reduces the risk of failure in official inspections, accelerating the governmental approval process and the subsequent transfer of subsidies. Furthermore, the systematic implementation of pre-inspection audits critically mitigates the risk of losing tax credits and regulatory sanctions, establishing an essential governance mechanism. It is concluded that pre-inspection audits not only ensure immediate technical compliance but are fundamental for maintaining the long-term accessibility and durability of social housing, promoting efficiency in the allocation of public resources and improving the beneficiaries’ quality of life.